Minat Dan Aktivitas Gerak Siswa SMP N 2 Kandangan Dalam Pembelajaran Penjas Daring Pada Masa Pandemic Covid-19 (Universitas Negeri Semarang, 2021)
The world of education is currently facing quite a complex problem, namely the Coronavirus Disesase (Covid-19). During the COVID-19 Pandemic, the government in Indonesia has provided rules to close schools in the red and yellow zones and conduct distance learning at home, one of which is SMP Negeri 2 in Kandangan District has also decided to implement a learning policy, one of which is the Sports Physical Education subject. and Health (PJOK) from home as a form of emergency response to prevent the spread of the corona virus. However, students experienced obstacles, namely that not all students had smartphones, internet quotas, and difficulty in signal networks. The purpose of this study was to describe and study students' interests and movement activities in learning physical education class VIII at SMP Negeri 2 Kandangan during the Covid-19 pandemic. This research is a type of qualitative research with a descriptive approach. The results of the research were the implementation of PJOK learning during this pandemic, students were less happy and less interested because students were bored with online learning methods, students had difficulty understanding the learning material and students were less actively involved in learning. In terms of movement activities, students are not maximal in doing so, students are less able to capture examples of movements that are given online. The conclusion of this study was that grade VIII students at SMP N 2 Kandangan were less interested in participating in online Physical Education learning during the Covid-19 pandemic.